Teachers’ Perceptions of Digital Technology Use in English Language Learning During The Covid-19 Pandemic and in The Post-Pandemic Period - Annisa Afrilianti; Hasbi Sjamsir; Iwan Setiawan; Didik Sucahyo; Bibit Suhatmady (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2025)
COVID-19 brings a deep impact on the field of education, especially by pushing the wide use of digital technology in learning. When face-to-face learning returned, it became important to see whether teachers’ experiences with technology during the pandemic affected their views and decisions about using technology after the pandemic. Many studies have looked at teachers’ views during and after the pandemic, but only a few have explored how English teachers view these experiences and how it influenced their decisions to keep or change their use of technology especially in schools located outside urban centers or in areas with limited resources. This research focused on exploring the views of English teachers on using digital technology during and after the COVID-19 pandemic at a semi-rural public Junior High School in East Kalimantan. This study used a descriptive qualitative method with in-depth interviews for data collection. The results showed that before the pandemic, most teachers only used technology as a supporting tool. After the pandemic ended and learning returned to the classroom, teachers tend to continue the use of technology because they found it helpful and had become accustomed to it, although the use of technology after pandemic less frequent compared to during the pandemic.